2020
DOI: 10.1186/s12879-020-05294-y
|View full text |Cite
|
Sign up to set email alerts
|

Orbital abscess caused by Exophiala dermatitidis following posterior subtenon injection of triamcinolone acetonide: a case report and a review of literature related to Exophiala eye infections

Abstract: Background: Subtenon injection of triamcinolone acetonide (STTA) has been widely adopted in the clinical setting of ophthalmology and its infectious complications are rare. However, orbital abscess following STTA has been reported in seven cases. Furthermore, although eye infections due to Exophiala species are uncommon, there have been 19 cases to date. E. jeanselmei, E. phaeomuriformis, E. werneckii, and E. dermatitidis have been reported to cause human eye infections; however, to the best of our knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Despite intravitreal injections for retinal disease becoming the most commonly performed intraocular procedure globally [ 155 ], and corticosteroid periocular injections being used routinely for the treatment of diabetic macular oedema [ 156 , 157 ], there have been no cases of fungal keratitis associated with this treatment reported in the scientific literature to date. However, other complicating local fungal infections have been reported, including fungal endophthalmitis, fungal orbital abscesses and conjunctival mycetoma [ 158 , 159 , 160 ].…”
Section: Epidemiology Of Fungal Keratitismentioning
confidence: 99%
“…Despite intravitreal injections for retinal disease becoming the most commonly performed intraocular procedure globally [ 155 ], and corticosteroid periocular injections being used routinely for the treatment of diabetic macular oedema [ 156 , 157 ], there have been no cases of fungal keratitis associated with this treatment reported in the scientific literature to date. However, other complicating local fungal infections have been reported, including fungal endophthalmitis, fungal orbital abscesses and conjunctival mycetoma [ 158 , 159 , 160 ].…”
Section: Epidemiology Of Fungal Keratitismentioning
confidence: 99%
“…and one case of orbital abscess due to Exophiala dermatitidis after subtenons steroid injection. 10 The authors’ review of cases of orbital abscess after posterior subtenons injections revealed bacterial abscess developed within 4–6 weeks, whereas fungal orbital abscess took 2–3 months to develop.…”
Section: Discussionmentioning
confidence: 99%
“…The most common manifestations of the infection are skin infections; in addition, less commonly, extracutaneous diseases from traumatic implantation have been reported, including the eyes, heart, gastrointestinal tract, lungs, and bones[ 3 , 4 , 14 , 22 , 25 , 26 ]. The fungus can actively grow and penetrate the skin; consequently, it is more frequently isolated from superficial, cutaneous, subcutaneous, and deep seated infections, including visceral infections, with central line associated bloodstream infection (CLABSI) or endocarditis seen on rare occasions[ 11 , 25 , 27 - 29 ].…”
Section: Symptomsmentioning
confidence: 99%